MORPHOLOGICAL ASPECTS OF DAMAGE TO THE GLANDULAR STROMA IN VARIOUS FORMS OF SAFE HYPERPLASIA OF THE PROSTATE - Khamraev Obidjon Ashurmamatovich (Scholar Express Journals, 2024)
The human prostate gland is one of the only internal organs that continue to enlarge throughout adulthood. The specific mechanisms that regulate this growth, as well as the pathological changes leading to the phenotype observed in the disease benign prostatic hyperplasia (BPH), are essentially unknown. Recent studies and their associated findings have made clear that many complex alterations occur, involving persistent and chronic inflammation, circulating hormonal level deregulation, and aberrant wound repair processes. BPH has been etiologically characterized as a progressive, albeit discontinuous, hyperplasia of both the glandular epithelial and stromal cell compartments coordinately yielding an expansion of the prostate gland and clinical symptoms.
Keywords: reactive stroma; BPH; tenascin-C; hyperplasia